Bilateral cardiac sympathetic denervation of a recurrent refractory ventricular tachycardia occurring after catheter ablation of atrial fibrillation and outflow tract premature ventricular contractions. Issue 2 (30th January 2019) - Yagishita, Atsuhiko; Goya, Masahiko; Takahashi, Yoshihide; Ishibashi, Hironori; Akiyoshi, Kikou; Sekigawa, Masahiro; Maeda, Shingo; Kawabata, Mihoko; Okubo, Kenichi; Hirao, Kenzo
Abstract: Recent studies have demonstrated the utility of cardiac sympathetic denervation (CSD) in patients with ventricular tachycardia (VT) refractory to antiarrhythmic drugs and catheter or surgical ablation. We present our experience with bilateral CSD in a patient with a recurrent VT despite attempts at treatment with catheter ablation and antiarrhythmic drugs, and this is the first description of the successful management of an idiopathic refractory VT with a bilateral CSD and concomitant oral amiodarone, occurring after catheter ablation of persistent atrial fibrillation and idiopathic outflow tract premature ventricular contractions.